Design a broadband low noise amplifier for software radio receiver application - Mohamed, Yazid (Penerbit UTM Press, 2000)
This report describes the design of a broadband low noise amplifier (LNA) for the frequency range from 800MHz to 2GHz, using a microwave transistor. Tbe passive components were implemented using microstrips. The complete circuit design tbrough tbe use of a simulation software package of LNA has been achieved. Within the operational frequency band, the minimum achieved power gain is lOdB and the noise figure (NF) is within O.5dB from the minimum NF of the transistor.